ANALYZING GENERATION Z CHARACTERISTICS AS LIBRARY INTERIOR DESIGN PREFERENCES - Hadiansyah, Mahendra Nur; Salimah, Nabila Hana (Ide dan Dialog Desain Indonesia (Idealog), 2023)
Library as a public place with facilities that meet the needs of education, research, informationpreservation and user recreation has an important role in the growth of generation Z in Indonesia. However, as a place that can accommodate the various productive activities of generation Z, libraries are still of little interest to generation Z. Therefore, it is necessary to analyze the character of generation Z and its application into a library interior design with the aim of making the library interior in accordance with their needs and character so that the library can be more attractive to generation Z. This research was conductedqualitatively at selected locations where the productive Generation Z carried out their activities at several locations in the city of Bandung. There are stages through several methods including literature study, observation, and questionnaires, then further analyzed using the comparison matrix method fromthe datathat had been obtained. The results of the study found that there are several aspects in the library interior that can be adapted to the character of generation Z, first is the character of phigital, practical andindependent with the provision of digital-based facilities, then the character likes to interact with the application of dynamic layouts in reading and study areas, as well as the provision of webcams and LCDs tosupport remote interaction, then the creative and innovative character with the application of an attractive and not monotonous library atmosphere, next is the character of multitasking with the provision of semiformal areas, then the last is the ambitious character with the application of the separation of noisy areas and quiet areas in the library area. Keywords: Generation Z, Preference, Design, Interior, Library